2005
DOI: 10.1002/er.1054
|View full text |Cite
|
Sign up to set email alerts
|

Electric load analysis using an artificial neural network

Abstract: SUMMARYLoad forecasting in the current, increasingly liberalized, electricity power market is of crucial importance as a means for producers to optimize and rationalize energy supply. A number of electric power companies are equipped to make forecasts with the aid of traditional statistical methods. This paper presents the use of an artificial neural net to an hourly based load forecasting application for a small electric grid on an Italian island (Lipari) not connected to the mainland. The aim was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
12
0
3
Order By: Relevance
“…The findings of this paper showed that the combination of fuzzy logic and neural networks was an appropriate approach for the assessment of water supply sustainability. Cavallaro [23] used the neural network for a load application prediction of a small electric grid. The outcomes of this paper demonstrated that the proposed model was effective and had better performance compared with the traditional statistical approaches.…”
Section: Sustainability and Fuzzy Neural Networkmentioning
confidence: 99%
“…The findings of this paper showed that the combination of fuzzy logic and neural networks was an appropriate approach for the assessment of water supply sustainability. Cavallaro [23] used the neural network for a load application prediction of a small electric grid. The outcomes of this paper demonstrated that the proposed model was effective and had better performance compared with the traditional statistical approaches.…”
Section: Sustainability and Fuzzy Neural Networkmentioning
confidence: 99%
“…For example an industrial consumer consume more power during morning hours where as residential consumer consume more 978-1-4799-6042-2/14/$31.00 ©2014 IEEE power in evening. The important factors that should be taken into consideration for of electricity load forecasting can be classified as follows [7] • …”
Section: Factors Affecting the Electrical Loadmentioning
confidence: 99%
“…The traditional methods known as stochastic time series models (with the autoregressive integrated moving average [ARIMA] and the autoregressive moving average model with exogenous inputs [ARMAX] models being the most popular) are being compared and even replaced by artificial intelligence–based methods. In the last two decades, the artificial neural networks (ANNs) became by far the most common methodology adopted in electricity load forecasting, having already proven considerable benefits in modeling the load behavior based on historical patterns .…”
Section: Introductionmentioning
confidence: 99%